Sport, social development and peace - Young, Kevin, 1959-; Okada, Chiaki, 1948- (Research in the sociology of sport ;, 2014)
This volume is part of the early systematic inquiry into the analysis of sport as a developmental device. The book features an international roster of global experts. The chapters represent three groups: theory and philosophy, empirical research in on-the-ground case studies, and those using circumspection to construct cases regarding evaluation.